PRODUKTIVITAS DAN BIAYA ALAT MUAT BONGKAR EXP-2000 - Wesman Endom; Zakaria Basari; Ishak Sumantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Loading and unloading works are intermediary activities in the logging operation. The logs after being felled/cut down in the forest will be of economic values when they cannot be brought to the inherent processing industrie. Lightweight and smallsize logs favor manual work in their handling as long as man power is available. Heavyweight and largesize logs, however, necessitate an auxiliary heavyduty equipment, since the manual work is sometimes no longer effective for loadingrelated operation, e.g. hoisting, placing, regulating their position, etc. The unloading of such logs, conversely, turns out to be easier, but can pose a dangerous threat. Therefore, cautious care is necessary.In dealing with loading/unloading problems as such particularly in plantation forest, a special equipment that is simple in design has been devised, called as Exp2000. The equipment, wich is powered by 11HP's diesel engine, can also perform the skiddingoperation. The overall cost in devising the Exp2000 's equipment was Rp. 50,000,000. The trial test as performed on the equipment revealed the following results: .The average loading and loading productivities were consecutively 9.54 m3 per hour and 13.18 m3 per hour.Cost of loading as well as unloading was Rp. 1.597,48 per m3.The average skidding productivity was 0.5053 m3.hm/hour with skidding cost at Rp 30,160 per m3.The skidding cost might be reduced to Rp. 21,165 per m3 and concurrently the productivity increased to 2.25 m3per hour, if the more powerful diesel engine, e.g. 25 HP were used.